2019
DOI: 10.3390/ani9100715
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Genetic Parameters for Reproductive Traits in Hanwoo (Korean Cattle)

Abstract: Simple SummaryDue to the extensive marbling of its beef, Hanwoo (Korean native cattle) has continuously gained popularity and has become a mainstay in South Korea’s animal industry. In any beef cattle production system, reproductive performance is one of the main economic aspects taken into consideration. Therefore, genetic parameter estimates are necessary to obtain indices in order to maximize the response to selection, which in turn could lead to higher profitability. To date, knowledge on the genetic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
3
22
1
1
Order By: Relevance
“…This has been confirmed by our analysis and by many other authors. Martínez-Vélázquez et al [ 25 ] and Lopez et al [ 26 ] published heritability below 0.1. The heritability coefficient found in our study was similar to Veselá et al [ 21 ] 0.23; Buzanskas et al [ 3 ] 0.25; Berry and Evans [ 13 ] 0.31.…”
Section: Resultsmentioning
confidence: 99%
“…This has been confirmed by our analysis and by many other authors. Martínez-Vélázquez et al [ 25 ] and Lopez et al [ 26 ] published heritability below 0.1. The heritability coefficient found in our study was similar to Veselá et al [ 21 ] 0.23; Buzanskas et al [ 3 ] 0.25; Berry and Evans [ 13 ] 0.31.…”
Section: Resultsmentioning
confidence: 99%
“…The AFC was determined by determining the birthdate of the heifer and the date of its first calving, while the GL was computed using the last date of insemination and the calving date. Additional details for AFC and GL can be found in our previous studies [ 13 ]. Furthermore, the 9 generation-deep pedigree data consisted of 66,736 animals with 543 bulls, and 20,006 dams were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The covariance between the direct and maternal genetic effects was set to zero. Moreover, similar in our previous study [ 13 ], the additive genetic and residual effects were used as random effects for the analysis of AFC while additive genetic, permanent environmental, and residual effects were used for GL.…”
Section: Methodsmentioning
confidence: 99%
“…Indicators including age at first calving, days from calving to first breeding, days open, the length of the calving interval, pregnancy rates, and the number of services per conception can be used to evaluate the reproductive performance in dairy cows [10][11][12]. Although studies have shown the existence of genetic variance for reproductive performance, the additive genetic variance reported accounted for only a small fraction of the total variance [13][14][15]. There are strong motives for including reproductive performance in genetic selection programs of dairy cows, but the very low heritability estimates reported for most of the considered reproductive performance measures makes selection for reproductive performance not effective enough [9,16].…”
Section: Introductionmentioning
confidence: 99%